Young People’s Emotional Intelligence and Type of Interpersonal Behavior with Different Sociometric Status - Kochetova Yu.A.; Klimakova M.V. (Психолого-педагогические исследования)
The development of emotional intelligence in early adolescence is important and urgent problem, since at this age the need for communication is actively realized, manifesting itself in behavioral patterns as types of interpersonal behavior that poorly understood. The problem of the study is to identify components of emotional intelligence and types of interpersonal behavior of respondents with high and low sociometric status. Research hypothesis: the combination of the level of emotional intelligence components development and the prevailing types of interpersonal behavior are associated with the achievement of high or low sociometric status. The study sample consisted of 956 people: 456 girls (47.7%) and 500 boys (52.3%) aged 16-17. Research methods: a questionnaire of emotional intelligence "Emin" by D.V. Lyusin; test "The Interpersonal Diagnosis of Personality" by T. Leary; sociometry by J. Moreno in the adaptation by M.R. Bityanova. The relationship between emotional intelligence, the prevailing types of interpersonal behavior, and the sociometric status was studied using mathematical statistics methods of SPSS Statistics 20 program (cluster analysis procedure). Six clusters were identified. They describe the combination of components of emotional intelligence and the prevailing type of interpersonal behavior between young men and women with low and high sociometric statuses. Comparison of cluster indicators revealed significant differences at a high level of significance (α<0.01) across all scales. Thus, the hypothesis was confirmed. The research has a high practical significance because it opens up opportunities for the development of emotional intelligence, as well as the harmonization of interpersonal relations.